The Apparent uPA/PAI-1 Paradox in Cancer: More than Meets the Eye - Kwaan, Hau C.; Mazar, Andrew P.; McMahon, Brandon J. (Seminars in Thrombosis and Hemostasis, 2013)
The expression of several components of the plasminogen–plasmin (P–P) system in tumor tissues has been shown to have prognostic significance in many human cancers, including those of the breast, prostate, lung, brain, ovary, stomach, colon, rectum, oral cavity, kidney, and bone. Mechanisms of action of the individual components have been extensively studied in tumor cells in vitro and in animal models. By interrupting various putative pathways involved in tumor progression in several experimental tumor models in animals, varying degrees of tumor control have been achieved. However, these efforts have thus far not been able to exert any impact in oncologic clinical practice. A possible explanation is our incomplete understanding of the complex involvement of the P–P system and its interactions with other tumorigenic factors. In this article, the role of various members of the P–P system in cancer is reviewed. Proteolysis via the urokinase-type plasminogen activator–plasminogen activation pathway tends to enhance tumor growth and invasion, and its natural inhibitor plasminogen activator inhibitor type 1 may also enhance tumor growth through the inhibition of apoptosis, enhancing cell proliferation and the promotion of angiogenesis. Meaningful drug designs for therapeutic intervention require a thorough understanding of the role of all of the components involved in this complex mechanism of tumor progression.
Keywords: uPA; PAI-1; uPA receptor; plasmin